Comparative randomized study on the sexual function and quality of life of women on contraceptive vaginal ring containing ethinylestradiol/etonogestrel 3.47/11.00mg or 2.7/11.7mg. (3rd October 2019) - Caruso, Salvatore; Panella, Marco; Giunta, Giuliana; Matarazzo, Maria Grazia; Cianci, Antonio
Abstract: The objective of the study was to evaluate the sexual function and quality of life (QoL) of healthy women on a new contraceptive vaginal ring (CVR) containing ethinylestradiol (EE) 3.47 mg and etonogestrel (ENG) 11.00 mg (study group) manufactured with a new polymer composition compared to EE 2.7 mg/ENG11.7 mg CVR (control group). Fifty-eight women were randomly allocated to the study group and the control group. The Female Sexual Function Index (FSFI), the Female Sexual Distress Scale (FSDS) and the Short Form-36, were used to assess sexual function, sexual distress and QoL, respectively. The study included two follow-ups, at 90 days and at 180 days. The control group reported more adverse events, mainly breakthrough bleeding, than the study group. The sexual function scores in the women in the study group improved with respect to those of the control group both at the 1st (FSFI, p = .009; FSDS, p = .001) and at the 2 nd (FSFI, p = .001; FSDS, p = .002) follow-up. QoL of the study group improved at the 1 st follow-up ( p < .05) and 2 nd ( p < .01) follow-up. The control group improved their QoL at the 2nd follow-up ( p < .01). The more gradual EE release of the new polymer composition could justify the behavioral differences of the women of the two groups.